2018
DOI: 10.1021/acs.analchem.8b03586
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Quantification of Uptake in Gram-Negative Bacteria

Abstract: Infections by Gram-negative pathogens represent a major health care issue of growing concern due to a striking lack of novel antibacterial agents over the course of the last decades. The main scientific problem behind the rational optimization of novel antibiotics is our limited understanding of small molecule translocation into, and their export from the target compartments of Gram-negative species. To address this issue, a versatile, label-free assay to determine the intracellular localization and concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 51 publications
3
86
0
2
Order By: Relevance
“…5 Where intracellular distribution studies have been conducted, they have largely relied on radioactive analogues, which are costly, difficult to access, and require specialist equipment. [10][11][12][13][14][15][16][17][18][19] Neither of these techniques readily allow for analysis at single-cell resolution, though some single cell sequencing reports are beginning to appear. 20,21 Despite the success of these approaches, there remains a significant appeal in simple tools that are readily accessible and do not require a large time or resource investment, or which can be utilised in combination with more modern technology, such as highresolution microscopy and single cell microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…5 Where intracellular distribution studies have been conducted, they have largely relied on radioactive analogues, which are costly, difficult to access, and require specialist equipment. [10][11][12][13][14][15][16][17][18][19] Neither of these techniques readily allow for analysis at single-cell resolution, though some single cell sequencing reports are beginning to appear. 20,21 Despite the success of these approaches, there remains a significant appeal in simple tools that are readily accessible and do not require a large time or resource investment, or which can be utilised in combination with more modern technology, such as highresolution microscopy and single cell microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] One of the current bottlenecks in the development of molecules active against Gram-negative bacteria is their low permeability across the bacterial cell wall, composed of an outer membrane (OM) and inner membrane (IM). 4,5 Methods to investigate the accumulation of antimicrobial agents inside a cell can be in vivo viability assay, 6 liposome swelling assay, 7 mass spectrometry and uorometry related approaches, [8][9][10] and electrophysiology. 5,11 Nanopore based single molecule tools could already investigate a single nucleotide segment, 12,13 and nucleotide base lesion analogues, 14,15 peptides [16][17][18][19] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The reported volume of the periplasmic space of Gram-negative bacteria ranges from 7% to 40% [ 20 , [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. A seminal study by Stock et al reported that the periplasmic space in E. coli and S. typhimurium constitute of approximately 20–40% of the total cell volume [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…When we first started this project, no publications were available to our knowledge that studied the accumulation of antibiotics in subcellular fractions of Gram-negative bacteria. A very recent report described fractionation and quantification of the antibiotic accumulation using mass spectroscopy [ 20 ]. The accumulation of four antibiotics from different classes were investigated.…”
Section: Introductionmentioning
confidence: 99%